Analysis of the Effect of Brand Loyalty on Perceived Quality with the Mediator Variable of Customer Authentic Perception - Kurniawan, Robby; Stanley, Vanessa (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Telecommunication technology is developing rapidly, triggering fierce competition in the hospitality industry. A deep understanding of customer needs and appropriate product development are essential to win this competition. This study investigates the relationship between brand loyalty, brand image, brand awareness, and brand trust in the context of the smartphone industry. Brand loyalty is shaped by how consumers perceive a brand's image, their level of knowledge about the brand, and their trust in the brand. This study aims to provide significant insights for companies in formulating successful marketing strategies to improve their brand position in the competitive market. This study investigates the relationship between brand loyalty, brand image, brand awareness, and brand trust in the smartphone industry. By summarizing the findings of previous studies, this study proposes a model that clarifies the influence of these variables on brand loyalty. The findings of this study are expected to provide valuable insights for companies in designing more effective marketing strategies to strengthen their brand position in the competitive market.